2017
DOI: 10.1002/app.45050
|View full text |Cite
|
Sign up to set email alerts
|

Orientational behaviors of silk fibroin hydrogels

Abstract: In this study, a novel shear‐induced silk fibroin (SF) hydrogel with three‐dimensional (3D) anisotropic and oriented gel skeleton/network morphology is presented. Amphipathic anionic and nontoxic sodium surfactin is blended with the SF to decrease its gelation time during the mechanical shearing process. The fibroin/surfactin blended solutions undergo a facial shearing process to accomplish a sol–gel transition within 1 hour. The dynamic sol–gel transition kinetic analysis, gel skeleton/network morphology, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Although multiple cues such as stiffness, compositions and nanostructures have significant influence on cell proliferation, the cell culture results on RSF-SNF hydrogels indicated that the introduction of SNF resulted in a better niche for cell response in vitro , which is similar to several studies that revealed an enhanced influence of nanofibrous SF materials on cell compatibility. 28,4749…”
Section: Resultsmentioning
confidence: 99%
“…Although multiple cues such as stiffness, compositions and nanostructures have significant influence on cell proliferation, the cell culture results on RSF-SNF hydrogels indicated that the introduction of SNF resulted in a better niche for cell response in vitro , which is similar to several studies that revealed an enhanced influence of nanofibrous SF materials on cell compatibility. 28,4749…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic molecular conformation of HSF samples (5 mg/mL) at 50 °C was measured using a circular dichroism (CD) spectrometer (JASCO, Japan). After incubation at 50 °C, the samples were added into a quartz cuvette with a thickness of 0.1 mm, and the ultraviolet polarizing spectrum was scanned in the wavelength range of 190–250 nm. The measurement temperature was 25 °C, the broadband was 1.00 nm, the wavelength step was 0.20 nm, and the response time was 0.33 s. The CD of deionized water was also determined under the same experimental conditions, and the value was subtracted from the final result.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the unique temperature-dependent gelation properties, gelatin, and GelMA are widely used for 3D printing applications. For GelMA, by introducing and regulating photoinitiators and employing light exposure (such as UV light, blue light, or white light), the methacrylamide and methacrylate [100][101][102] Copyright 2018, Wiley-VCH; Copyright 2018, American Chemical Society; Copyright 2018, Wiley-VCH. d) Fabrication of graphene/silk fibroin-based conductive hydrogels under electric field stimulation.…”
Section: Gelatin and Its Nanocompositesmentioning
confidence: 99%